2013
DOI: 10.4236/jbbs.2013.38067
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Recovery of Cognitive Function in Stroke

Abstract: Hippocrates (460-377 BC) first described stroke over 2400 years ago. Stroke is the 4 th leading cause of death in Canada (3 rd in the USA) and the primary cause of permanent motor and cognitive disability. The majority of strokes are ischemic. The extent of cerebral dysfunction and thus the severity of stroke are based on the location, severity and duration of ischemia. Stroke management and prognosis encompass early recognition of the onset of stroke and post-stroke determination of the extent of brain injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Although resting-state fMRI can elucidate the brain's functional connections by determining temporal synchrony between brain regions, whether the training-induced changes in the neural activity associated with cognitive training remains unexplored. Event-related fMRI with BOLD contrast technique might be better in representing functionality of brain regions at least in normal subjects performing various cognitive tasks [ 59 ]. To the best of our knowledge, only one case study investigated the patterns of neural activation after a course of auditory working memory training using event-related fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…Although resting-state fMRI can elucidate the brain's functional connections by determining temporal synchrony between brain regions, whether the training-induced changes in the neural activity associated with cognitive training remains unexplored. Event-related fMRI with BOLD contrast technique might be better in representing functionality of brain regions at least in normal subjects performing various cognitive tasks [ 59 ]. To the best of our knowledge, only one case study investigated the patterns of neural activation after a course of auditory working memory training using event-related fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…Many older people will not have a “normal” brain [21]; for many, a routine Computed Tomograph (CT) brain scan either before or after stroke reveals diffuse periventricular ischaemia [22]. These are associated with dementia, infection, Parkinsonism, motor disorders and stroke recurrence.…”
Section: Pre-stroke Functionmentioning
confidence: 99%
“…Stroke recovery requires neuroplasticity to occur, however animal studies have suggested that with increasing age there is a reduction in neurogenesis in basal hippocampus regions compared to striatal-like regions [63]. The presence of an ischaemic brain [22] pre-stroke status will affect post-stroke recovery; particularly executive functioning and memory task processing will be affected [22]. The presence of a high load of periventricular ischaemia would suggest a reduction in brain reserve, and hence the ability to rewire the brain [64,65] may be reduced [66].…”
Section: Outcomementioning
confidence: 99%